EXPRESSION OF ASTRONYMS IN UZBEKI THROUGH ZOOMORPHEMS (Spectrum Journal of Innovation, Reforms and Development, 2022)
This scientific article is devoted to the issues of using the names of animals, birds, and insects in the representation of astronomy. The breadth of possibilities of lexical units denoting the names of animals in representing celestial bodies is considered. The difference between concept and understanding is explained. Attention is paid to the reflection of the " Heavenly bodies" concept in zoomorphic images.